Dlaczego (auto)biografie? Literatura dokumentu osobistego kiedyś i dziś - ANNA PEKANIEC (Autobiografia, 2022)
This text is a review of selected ways of defining autobiography and biography, showing the specificity of each genre of personal writing, as well as indicating points of contact and exposing mutual dependencies. The (auto)biographical theories of e.g. Małgorzata Czermińska, Phillipe Lejeune, George Mish combined with theoretical approaches to biography by Jerzy Jarniewicz, Lucyna Marzec, Michał Paweł Markowski, complemented by a gender component, not omitting also the specificity of letters as a genre more strongly related to autobiography than biography, served to indicate the reasons for the permanent attractiveness of personal document literature. Moreover, by taking into account narrative theories of identity, an attempt was made to reconstruct possible constructions of the (autobiographical) subject. The whole article (in an extended version) was delivered as an inaugural lecture during the opening of the Biography and Autobiography Research Workshop at the Faculty of Polish Studies of the Jagiellonian University.